THE IMPORTANCE OF HETEROGENEITY OF HABITATS FOR THE SPECIES RICHNESS OF VASCULAR EPIPHYTES IN REMNANTS OF BRAZILIAN MONTANE SEASONAL SEMIDECIDUOUS FOREST - Barbosa, D. E. F.; Basílio, G. A.; Furtado, S. G.; Menini Neto, L. (Edinburgh Journal of Botany, 2019)
Epiphytes are an important component of the diversity of tropical forests, and they also have several ecological functions. Vegetation heterogeneity is one of the features responsible for the high biodiversity of the Atlantic Forest, especially in the domain’s seasonal semideciduous forest (SSF). This biodiversity presents as high endemism and species richness. Owing to the seasonal nature of SSF, organisms that require high humidity (e.g. epiphytes) would be expected to show low species richness in these forests. The aims of this study were to conduct a survey of the vascular epiphytes in remnants of montane SSF in the Serra do Ibitipoca, Brazil, and to evaluate the importance of habitat heterogeneity for the richness and composition of species in these areas. We also evaluated whether the intrinsic characteristics of the SSF phytophysiognomy and fragmentation could result in low species richness and a high number of accidental epiphyte species. The study was conducted in the course of 18 expeditions undertaken between September 2013 and December 2016, covering five fragments of montane SSF (totalling 23.6 ha). We recorded 96 species (only one of which is an accidental epiphyte), distributed across 41 genera and 10 families. This is the highest epiphytic species richness recorded in Brazilian SSF to date. The results refuted the initial hypothesis and reinforce the importance to the epiphytic community of conservation of fragments with different structures.
Keywords: Atlantic Forest; ferns; Orchidaceae; Serra da Mantiqueira; Serra do Ibitipoca